Gwendy's button box - King, Stephen, 1947-; Chizmar, Richard T. (Forest Hill, MD : Cemetery Dance Publications, 2017)
There are three ways up to Castle View from the town of Castle Rock: Route 117, Pleasant Road, and the Suicide Stairs. Every day in the summer of 1974 twelve-year-old Gwendy Peterson has taken the stairs, which are held by strong (if time-rusted) iron bolts and zig-zag up the cliffside. A stranger calls to Gwendy: "Hey, girl. Come on over here for a bit. We ought to palaver, you and me." On a bench in the shade sits a man in black jeans, a black coat like for a suit, and a white shirt unbuttoned at the top. On his head is a small neat black hat. The time will come when Gwendy has nightmares about that hat.
Keywords: Preteen girls -- Fiction; Castle Rock (Me. : Imaginary place) -- Fiction; Horror fiction; Novellas